Peran Orientasi Penjualan dan Orientasi Pelanggan Serta Penginderaan Pelanggan Terhadap Kinerja Tenaga Penjualan - Diana Aqmala (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2019)
One form of cooperation carried out by banking and insurance financial institutions is the existence of bancassurance. The success of the bancassurance concept depends very much on the performance of the sales force, which in this case is an employee of a banking financial institution. This study aims to analyze sales orientation, customer orientation, and customer sensing on sales force performance. The data collection method used in this study is the questionnaire method given to respondents. The population in this study is the AXA Mandiri insurance sales force in Central Java. Respondent criteria for the research sample are salespeople who are sole agents (do not work as insurance agents in more than one insurance company) and have worked as insurance agents for more than 1 (one) year. Based on the results of the analysis show that sales orientation has no effect on sales force performance, customer orientation and customer sensing have a positive and significant effect on sales force performance. The variable that provides the highest influence on salesperson performance is customer orientation.One form of cooperation carried out by banking and insurance financial institutions is the existence of bancassurance. The success of the bancassurance concept depends very much on the performance of the sales force, which in this case is an employee of a banking financial institution. This study aims to analyze sales orientation, customer orientation, and customer sensing on sales force performance. The data collection method used in this study is the questionnaire method given to respondents. The population in this study is the AXA Mandiri insurance sales force in Central Java. Respondent criteria for the research sample are salespeople who are sole agents (do not work as insurance agents in more than one insurance company) and have worked as insurance agents for more than 1 (one) year. Based on the results of the analysis show that sales orientation has no effect on sales force performance, customer orientation and customer sensing have a positive and significant effect on sales force performance. The variable that provides the highest influence on salesperson performance is customer orientation.